Mechanical Properties of Lightweight Foamed Concrete with Utilization of Agro-waste as Supplementary Cementitious Material: A Review - LAU WEN WEN, JACQUELINE; Mohamad , Noridah (Recent Trends in Civil Engineering and Built Environment, 2022)
Agricultural waste, in particular, has been widely used as supplementary cementitious materials (SCM) in concrete production, which helps to reduce the carbon dioxide emissions (CO2) from the cement industry. This paper focuses on the effects of palm oil fuel ash (POFA), oil palm ash (OPA) and eggshell powder (ESP) as partial cement replacement on the mechanical properties, workability and water absorption of lightweight foamed concrete (LFC). Previous experimental studies and researches are the credible sources for this review paper. From the findings, most of the reviews proved that utilization of these agro-waste powders could improve the compressive strength, flexural strength and splitting tensile strength of LFC. From overall reviews, it found that the presence of agro-waste in LFC caused a reduction in the workability and water absorption. The optimum percentage ranges for POFA or OPA was 20% to 35% and for ESP was 5% to 7.5%. Meanwhile, up to 25% of combined POFA and ESP have proven to enhance the strength properties of LFC.